PENGARUH KEADILAN,DISKRIMINASI, DAN PENALTY RATE TERHADAPpPERSEPSI WAJIP PAJAK ORANGpPRIBADI MENGENAI ETIKA PENGGELAPAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA SURAKARTA - Desya Noveria Revitasari; Fadjar Harimurti; Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Analyzegthegsignificance of theneffect of justice, discriminationhand penalty rates on perceptionscof individualgtaxpayers regardingcthe ethics ofntax evasion. Data obtainedgthrough observation,ninterviews, distributiongof questionnaires, and.taking.documentation. Datapobtainedkthrough.the.distribution.of questionnaires to individual taxpayersgof thegSurakrta Pratama Tax Office. Thensample gused was a taxpayer in the city of Surakarta, whichkamounted to 100krespondents. Refinement technique in this research iskpurposivedsampling technique. The analyticalctool used isgmultiple linear regression. The resultsgof the studygconcluded that: 1). There is avsignificant effect of justice on thegethical perceptionsvof tax evasion, 2). There is agsignificant effect of discriminationkon ethicaldperceptions of tax evasion, and 3). .Therekispa significant effectkof penalty rates on ethical perceptions fof jtaxjevasion.